Methodology Development for Designing Energy Efficient Distillation Column Systems - Mohd Faris, Mustafa (Elsevier Ltd, 2014)
Distillation is the primary separation process widely used in the industrial chemical processing. Although it has many advantages, the main drawback is its large energy requirement, which can significantly influence the overall plant profitability. However, the large energy requirement of these processes can be systematically reduced by using driving force and energy integration methods. This paper presents a methodology development for designing energy efficient distillation column systems based on those two methods. Accordingly, the proposed methodology consists of four hierarchical steps. In the first step, the system of distillation column for multicomponent separation is designed based on the conventional distillation column design method. Then, the conventional distillation columns systems design is improved in terms of energy saving by using driving force method in the second step. It is expected in the third step that the distillation columns systems design can be further improved in terms of energy saving by using energy integration method. Finally, the distillation column systems design is evaluated in in terms of economic performance. By applying the proposed methodology, it is possible to make an early assumption on sequence of distillation column systems that is the best in terms of energy saving.